Actuarial resources in high demand, what makes them stay? - Muzondo, Lyn Nyasha (School of Management Studies, 2019)
The shortage of qualified actuaries and actuarial science resources in general, remains a challenge for organisations operating in the South African financial and insurance sectors. Access to such resources are a business imperative for these organisations and, therefore, there is a compelling business case to better understand which total rewards elements contribute most to the retention of individuals that possess these critical and also scarce skills. Furthermore, it would seem that traditional strategies that are meant to retain actuaries and/or actuarial science resources are no longer effective and new and innovative approaches in terms of their design and implementation need to be found. The aim of the present study was, therefore, to investigate the retention of actuarial resources and identify the total rewards elements that will be most useful in creating the conditions that are conducive for them to stay within their respective organisations. Limited research in which the total rewards elements that may contribute most to the retention of actuarial resources, could be found. Greater insight in this area will hopefully enable organisations to develop reward policies and practices that are able to more effectively attract and retain actuarial resources. A descriptive research design and quantitative approach was employed to estimate the total rewards preferences of actuaries, in other words which reward elements they would prefer and that may be related to their intention to stay. Using a non-probability convenience sampling approach, primary data was collected by means of an online field survey (n = 135). The questionnaire that was used to collect data, included a total rewards sub-scale (21 items), a reward preferences sub-scale based on best-worst scaling (10 items), a job satisfaction subscale (6 items), an intention to stay sub-scale (4 items), an affective commitment sub-scale (6 items) and a single open-ended question, which was optional. Data was analysed using descriptive statistics, factor analysis, assessing reliability using Cronbach’s alpha and conducting inferential statistics. The results of the factor analysis indicated that the total rewards dimensions do not influence intention to stay of the participants. Although job satisfaction and affective commitment were found to be significantly positively related to intention to stay, these variables were not found to mediate the relationship between total reward elements and intention to stay. The best-worst scaling results revealed that all participants considered remuneration and career advancement to be the most important total reward element for their intention to stay. For all generational groups, the bottom three reward elements (i.e. ranked) were learning opportunities, performance recognition and employee benefits, respectively. Traditional reward elements are important to employees with scarce skills. However, customizing reward preferences according to the generational preferences would enable an innovative approach to talent retention of actuarial resources.